2020
DOI: 10.1111/pce.13783
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of elevated CO2, warming, reduced rainfall, and nitrogen on leaf gas exchange in five perennial grassland species

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 73 publications
1
20
0
Order By: Relevance
“…Future reductions in the forage quality of sourveld and sweetveld will depend on how other major climate change drivers (temperature and precipitation) interact with the carbon fertilisation effect (CFE) to alter the balance between plant growth-driven demand for, and soil supply of, nutrients, primarily N. 6,7,12 The CFE would be most pronounced when resources and environmental conditions do not restrict plant growth. 19 However, the effects of multi-way interactions between climate drivers on plants and soils, particular on forage quality, are poorly understood; these interactions can be complex, multiplicative 20,21 , and species-specific 22 . Given these uncertainties and the current growth limitations prevailing in sour- and sweetveld 11,12 , we tentatively predict the following potential shifts in plant quality (leaf [N], digestibility, and fibre content) under climate change.…”
Section: Discussionmentioning
confidence: 99%
“…Future reductions in the forage quality of sourveld and sweetveld will depend on how other major climate change drivers (temperature and precipitation) interact with the carbon fertilisation effect (CFE) to alter the balance between plant growth-driven demand for, and soil supply of, nutrients, primarily N. 6,7,12 The CFE would be most pronounced when resources and environmental conditions do not restrict plant growth. 19 However, the effects of multi-way interactions between climate drivers on plants and soils, particular on forage quality, are poorly understood; these interactions can be complex, multiplicative 20,21 , and species-specific 22 . Given these uncertainties and the current growth limitations prevailing in sour- and sweetveld 11,12 , we tentatively predict the following potential shifts in plant quality (leaf [N], digestibility, and fibre content) under climate change.…”
Section: Discussionmentioning
confidence: 99%
“…Despite that, elevated CO 2 (eCO 2 ) is believed to increase the photosynthetic rate and suppress their photorespiration ( Li et al, 2019 ). eCO 2 increased the photosynthesis and stimulated biomass and yield parameters ( Kirschbaum, 2011 ) along with decreased water use per unit area of vegetation by partial stomatal closure ( Pastore et al, 2020 ). Studies have also shown that eCO 2 causes a 20–30% increase in net assimilation rate, together with an increase in dry matter and yield of crops ( Cruz et al, 2018 ; Pan et al, 2018 ; Xie et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, eCO 2 and water stress, sowing to climate change, can directly affect plant physiology and morphology ( Lobell and Gourdji, 2012 ; Salazar-Parra et al, 2012 ). It is postulated that because invasive species benefit from eCO 2 , this will enable them to acclimatize to their new environments in the future ( Dukes et al, 2011 ; Pastore et al, 2020 ). It is predicted that rising atmospheric CO 2 may cause global warming, which could be the basis of change in precipitation patterns and drought occurrence, and could possibly affect those regions not currently subjected to drought ( Robredo et al, 2007 ; Dai, 2013 ; Dai et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations